Lacertus syndrome in a male collegiate tennis athlete: A level 4 case report - Richardson, L. N.; Lopez, R. M.; Wilson, B. B.; Tritsch, A. J.; Cohen, G. W. (International Journal of Athletic Therapy & Training, 2025)
A 24-year-old male collegiate tennis athlete presented with pain, weakness, and numbness consistent with the ulnar nerve distribution in the left distal upper extremity following excessive wrist and forearm flexion and pronation. The patient was diagnosed with lacertus syndrome after referral for imaging. Lacertus syndrome is an exertional compartment syndrome of the forearm, typically including median nerve entrapment and surgical intervention. The uniqueness of this case included ulnar nerve involvement and resolution with interprofessional conservative management. Athletic trainers should consider including other health care professionals to conservatively manage lacertus syndrome in patients with delayed symptom onset during repetitive wrist and forearm activities.